Hattin, 1187 Saladin's greatest victory - Nicolle, David 1944- (Campaign (Osprey Publishing), 2011)
In 1187, Christian Europe was shaken by events in the Middle East. This volume tells the story of those momentous months - the campaign leading to the Muslim capture of Jerusalem after the disastrous Crusader defeat at Hattin where, in a two day running battle on the waterless plateau between Saffuriya and Tiberias, beneath a burning sun, Saladin's troops destroyed the Christian army. The disaster at Hattin resulted in the collapse of the kingdom of Jerusalem and sparked off the Third Crusade under Richard I 'Coeur de Lion'. This book examines Hattin in detail and looks at the consequences of the battle.